KEBEBASAN BERSERIKAT BAGI PEKERJA YANG DIPEKERJAKAN SECARA KONTRAK (PKWT) (Lex Jurnalica, 2017)
AbstractILO Convention No. 87 on Freedom of Association states that freedom of association is applicable to all workers, including that this guarantee is provided without discrimination of employment, sex, color, race, creed / religion, nationality, or political views, and so on. The problem is how the right of association and association for workers with Certain Time Working Agreement (PKWT), according to Law No. 21 of 2000 on trade / labor unions and any constraints that may arise for trade unions or for the workers themselves, if a worker with a PKWT form becomes a member / union / trade union official. To solve this problem, the author uses normative- research method. The result is that the Author finds the reality that the right to organize and organize, especially for certain time workers / PKWT in practice, there is an obstacle to freedom of association and association. The authors conclude that there is a distinction between freedom of association and association for certain time workers / PKWT with permanent workers/PKWTTs, as certain time workers / PKWT are in a weak position in the employment relationship. That is the main obstacle in freedom of association and association that mandated by Law no. Law No. 21 of 2000 on Trade Unions which in practice cannot be fully implemented by workers, especially for PKWT workers, because there is still a sense of fear that their contracts will be terminated / not renewed if involved in trade union activities. Keywords: Freedom of association, employee, certain time work agreement AbstrakKonvensi ILO No. 87 tentang Kebebasan Berserikat menyatakan bahwa kebebasan berserikat berlaku bagi semua buruh tak terkecuali, bahwa jaminan ini diberikan tanpa mengenal diskriminasi atas pekerjaan, jenis kelamin, warna kulit, ras, keyakinan/agama, kewarganegaraan, ataupun pandangan politik, dan lain sebagainya. Permasalahannya bagaimana hak-hak berserikat dan berorganisasi bagi pekerja dengan Perjanjian Kerja Waktu Tertentu/PKWT, di tinjau dari Undang-Undang No. 21 tahun 2000 tentang serikat pekerja/serikat buruh dan Kendala – kendala apa aja yang mungkin timbul bagi serikat pekerja/serikat buruh atau bagi pekerja itu sendiri, apabila seorang pekerja dengan bentuk PKWT menjadi anggota/atau pengurus serikat pekerja/serikat buruh. Untuk menjawab permasalahan ini, penulis menggunakan metode penelitian penelitian normatif–empiris. Hasilnya adalah Penulis menemukan suatu kenyataan bahwa hak berserikat dan  berorganisasi khususnya bagi pekerja waktu tertentu/PKWT dalam praktiknya terdapat suatu hambatan terhadap kebebasan berserikat dan berorganisasi tersebut. Penulis menyimpulkan terdapat perbedaan antara kebebasan hak berserikat dan  berorganisasi  bagi pekerja waktu tertentu/PKWT dengan pekerja waktu tidak tertentu/PKWTT, karena pekerja waktu tertentu/PKWT berada dalam posisi yang lemah dalam hubungan kerja. Bahwa kendala utama dalam kebebasan berserikat dan berorganisasi yang diamanatkan oleh Undang-Undang No. 21 tahun 2000 tentang Serikat Pekerja/Serikat Buruh dalam praktiknya belum bisa dijalankan sepenuhnya oleh pekerja/buruh, terutama bagi pekerja PKWT, karena masih ada rasa ketakutan kontraknya akan diputus/tidak diperbaharui bila terlibat dalam kegiatan serikat pekerja/serikat buruh. Kata Kunci: Kebebasan berserikat, pekerja, PKWT